2018
DOI: 10.1111/jgh.14050
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of endoscopic preoperative biliary drainage for malignant hilar biliary obstruction: E‐POD hilar study

Abstract: Our retrospective analysis did not demonstrate the advantage of ENBD over EBS as the initial PBD for resectable hilar MBO. Although the technical success rate of endoscopic PBD was high, its re-intervention rate was not negligible, and unplanned re-intervention was associated with a poor prognosis in resected hilar MBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
2
25
1
7
Order By: Relevance
“…Nakai et al also reported that unplanned re-intervention was associated with a poor prognosis in patients with MHBO resected. 9 The present study showed that the independent predictive factors of dysfunction of initial EBD were BC-IV and pre-EBD cholangitis. Therefore, the patients with such factors should undergo as early radical surgical resection as possible, or bilateral EBD should be considered at an early stage.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Nakai et al also reported that unplanned re-intervention was associated with a poor prognosis in patients with MHBO resected. 9 The present study showed that the independent predictive factors of dysfunction of initial EBD were BC-IV and pre-EBD cholangitis. Therefore, the patients with such factors should undergo as early radical surgical resection as possible, or bilateral EBD should be considered at an early stage.…”
Section: Discussionsupporting
confidence: 51%
“…There have been several studies that focused on complications caused by EBD and need for re-intervention. [6][7][8][9][10] During the preoperative waiting period, dysfunction of EBD frequently results in the need for biliary re-interventions and postponement of surgery, occasionally leading to abort of surgery due to tumor progression. However, few studies have focused on the risk factors for dysfunction of EBD in patients with MHBO.…”
Section: Introductionmentioning
confidence: 99%
“…From the 9 studies, 813 cases in the ENBD group and 622 cases in the EBS group were used in this metaanalysis [8][9][10][11][12][13][14][15][16]. Low heterogeneity (I 2 = 19%, P = 0.27) was found, so we chose a random-effect model to pool the RR.…”
Section: Incidence Of Preoperative Cholangitismentioning
confidence: 99%
“…On the other hand, the technical rate of success of preoperative ENBD was higher. Its re-intervention rate had not been diminutive and unexpected re-intervention was confederated with a poor prognosis in resected hilar biliary obstruction [50]. Authors quoted that [50]; ENBD for hilar biliary obstruction currently requires re-interventions, equally in the planned and unexpected way.…”
Section: Endoscopic Retrograde Biliary Drainage (Erbd) or Endoscopic mentioning
confidence: 99%
“…Its re-intervention rate had not been diminutive and unexpected re-intervention was confederated with a poor prognosis in resected hilar biliary obstruction [50]. Authors quoted that [50]; ENBD for hilar biliary obstruction currently requires re-interventions, equally in the planned and unexpected way. It would need additional research in order to strengthen safety and efficiency of ENBD in those patients.…”
Section: Endoscopic Retrograde Biliary Drainage (Erbd) or Endoscopic mentioning
confidence: 99%